Hitler Youth : growing up in Hitler's shadow - Bartoletti, Susan Campbell (New York : Scholastic Nonfiction, 2005)
A look at the lives of both Hitler Youth members and young people who resisted the Nazi movement in World War II.
Includes bibliographical references (p. 169-173) and index.
KK 04/01/05
12-19.
1219
Keywords: Hitler-Jugend -- Juvenile literature; Hitler-Jugend.; National socialism and youth -- Juvenile literature; Jewish youth -- Germany -- History -- 20th century -- Juvenile literature; Holocaust, Jewish (1939-1945) -- Germany -- Juvenile literature; Jewish children in the Holocaust -- Juvenile literature; National socialism; Jews -- Germany; Holocaust, Jewish (1939-1945) -- Germany